(3eMGSHI GdJcGdja Hjf GdfXQjI hGdJWHjb (B/s - (3GdJcQjJj, GSeGYjd jMjs ((3YeGf(B: s (3OGQ hecJHI GdMGeO(B, s, 2006)
(3eMGSHI GdJcGdja(B- (3JHhjHGJ(B- (3fXQjGJ GdJcGdja(B- (3YfUQ JcdaI GdehGO hGdQbGHI Ydjg(B- (3YfUQ JcdaI GdYed hGdQbGHI Ydjg(B- (3GdJcGdja GdUfGYjI GdZjQ eHGTQI hGdQbGHI Ydjg(B- (3fXGe GdChGeQ GdEfJGLj(B- (3JcGdja GdefJLGJ GdeTJQcI heYGdLJgG(B.s
Keywords: (3GdeMGSHIs; (3eMGSHI GdJcGdjas